2020
DOI: 10.1101/2020.10.31.20223776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell phone mobility data and manifold learning: Insights into population behavior during the COVID-19 pandemic

Abstract: As COVID-19 cases resurge in the United States, understanding the complex interplay between human behavior, disease transmission, and non pharmaceutical interventions during the pandemic could provide valuable insights to focus future public health efforts. Cell-phone mobility data offers a modern measurement instrument to investigate human mobility and behavior at an unprecedented scale. We investigate mobility data collected, aggregated, and anonymized by SafeGraph Inc. which measures how populations at the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…A correlation between changes in the amount of time spent at home, the workplace, and shopping, and rates of infection has been shown [8][9][10]. It has been shown that compliance rates for staying at home are not uniform across different regions [11]. Stagnation of economic activity with an increase in the number of infections has been observed based on night-time illumination and power consumption [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A correlation between changes in the amount of time spent at home, the workplace, and shopping, and rates of infection has been shown [8][9][10]. It has been shown that compliance rates for staying at home are not uniform across different regions [11]. Stagnation of economic activity with an increase in the number of infections has been observed based on night-time illumination and power consumption [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…During the final stages of processing, the hb_shrink function was used to perform hierarchical Bayesian shrinkage on the county-to-CBG level to improve the reliability of the estimates. SafeGraph's stay-at-home index has been used in many studies in order to analyze the impact of mobility patterns and physical distancing after the implementation of shelter-in-place policies in the USA [35][36][37]40].…”
Section: Methodsmentioning
confidence: 99%
“…t = T t−1 + t , where t = ( 1t , … , Kt ) t ∼ N(0, 2 Q W, S −1 )1 For an excellent tutorial on the methods used in this paper, see Lee, D (40)…”
mentioning
confidence: 99%
“…For example, citywide smart card travel data in Sydney, Australia, has been utilised to cluster passenger types along multiple mobility dimensions and develop intervention strategies for disease spread (Shoghri et al, 2020). Similarly, manifold learning techniques have been applied to cell-phone mobility data in the United States during the Covid-19 pandemic, distinguishing mobility trends in multiple geographic regions and demographics (Levin et al, 2020). Wisesty and Mengko (2021) leverage dimensionality reduction techniques to cluster and analyse highly dimensional genome sequence data of Covid-19.…”
Section: Introductionmentioning
confidence: 99%